Seasonal Variations of Zooplankton, Chlorophyll-A and Nutrients in Phewa Lake, Pokhara Valley, Nepal - Husen, Md. Akbal; Dhakal, Ram Prasad (Ecoprint: An International Journal of Ecology, 2010)
In order to understand trophic status of lake Phewa, largest lake (535 ha) in Pokhara valley, seasonal pattern of zooplanktons, chlorophyll a and nutrients level in water column was examined from January to December 2005. Total zooplanktons density was highest in January and November, showed bimodal pattern in Lake Phewa. The sequence of dominant species of zooplankton was Nauplius > Kerratella > Cyclops > Daphnia > Eodiaptomus in this lake. Correlation between zooplankton species and nutrients level was established. The Chlorophyll- a as an indicator of phytoplankton biomass peaks in November and chlorophyll-a concentration was found lower in winter months. The NH4-N ranged between zero to 0.021 mg/l with mean of 0.003 mg/l. The annual concentration of nitrate+nitrite (NO3+NO2) was found upto 0.148 mg/l (mean= 0.013 mg/l), soluble reactive phosphate (PO4-P) ranged from zero to 0.003 mg/l (mean= 0.001 mg/l), and total phosphorous ranged upto 0.052 mg/l (mean= 0.009 mg/l) in lake Phewa in 2005. Based on nutrients and chlorophyll-a dynamics, the lake varied from mesotrophic to eutrophic in different seasons. The Phewa Lake fluctuated from oligo-mesotrophic in monsoon seasons to meso-eutrophic in dry periods. Key words: Zooplanktons, nutrients, chlorophyll. DOI: 10.3126/eco.v16i0.3473 ECOPRINT 16: 51-57, 2009